Optional Protocol on the Sale of Children, Child Prostitution and Child Pornography – Criminalising Practices Including and Exceeding Exploitation and Abuse of Children - Stajnko, Jan; Fetai, Agnesa (International Children’s Rights, 2024)
The 2000 Optional Protocol to the Convention on the Rights of the Child on the sale of children, child prostitution and child pornography is considered one of the most widely ratified international treaties, promulgating the incrimination of customers and intermediaries in cases of sexual and other forms of exploitation of children. This chapter highlights its strengths and limitations. Special emphasis is placed on provisions prohibiting and criminalising practices covered under the Protocol, particularly concerning topical and divisive issues such as commercial surrogacy, virtual pornography and the maximum age of protection under the Optional Protocol. Moreover, topics such as sanctions and other substantive issues, jurisdiction, freezing and confiscation of assets, extradition and further instruments of mutual legal assistance, rights of child victims and preventive measures are briefly addressed. Where applicable, the contrast between the Convention and the Optional Protocol is emphasised, as the drafters of the latter opted for a more welfarist approach. This implies that the Optional Protocol drastically limits children’s agency to, for example, using explicit sexual materials in the context of sexting as a part of their sexual development. Recognising this issue, the authors argue against an unreasonably extensive interpretation of the Protocol’s provisions which concern practices that far exceed the exploitation or abuse of children. Keywords: trafficking, illicit trade, cybercrime, exploitation, commercial adoption, commercial surrogacy, international law